2020
DOI: 10.7819/rbgn.v22i3.4068
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of organisational professional conflict faced by professional accountants in different work settings

Abstract: Purpose-The aim of this study is to examine the effects of public interest commitment, professional commitment, organisational commitment, and organisational ethical culture on organisational professional conflict (OPC). The study also tests for the differences in the perception of OPC among professionals in different work settings: (i) professional accountants in business practice, (ii) tax and accounting advisors, and (iii) auditors. Design/methodology/approach-This study is based on a questionnaire distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Some authors pointed out pandemic effects on work organization and employee behaviour (Stanković & Radojević, 2022). Barrainkua & Espinosa-Pike (2020) show a negative relationship between individual organization commitment and organisational professional conflict (OPC) and between a strong organisational ethical culture and OPC. On the other hand, some studies found that plain-looking male accountants, who represent the traditional accountant stereotype, rarely behave unethically (Shtudiner & Klein, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors pointed out pandemic effects on work organization and employee behaviour (Stanković & Radojević, 2022). Barrainkua & Espinosa-Pike (2020) show a negative relationship between individual organization commitment and organisational professional conflict (OPC) and between a strong organisational ethical culture and OPC. On the other hand, some studies found that plain-looking male accountants, who represent the traditional accountant stereotype, rarely behave unethically (Shtudiner & Klein, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, to the extent that EC exists, it could negatively affect work-related attitudes and intentions, including CF. While previous scholars indicate that a higher level of auditor EC is associated with lower job satisfaction and higher turnover intentions (Barrainkua and Espinosa-Pike, 2020;Smith et al, 2020;El-Rajabi, 2007;Shafer et al, 2002;Bamber and Iyer, 2002), to our knowledge, no study has linked the EC with CF in auditing context. Therefore, based on the previous discussion, our third hypothesis will be as follow:…”
Section: Job Demandsmentioning
confidence: 72%
“…Participating in actions not consistent with the employees' ethical beliefs will create an unpleasant mental discord that he will seek to lower (Brief et al, 2001). EC increases when employees' personal values disagree with their organisation; accordingly, unfavourable consequences such as a lack of organisational identification, non-attendance, and TI may arise (Barrainkua and Espinosa-Pike, 2020;Smith et al, 2020;Thorne, 2001;Schwepker, 1999). The results of previous research support such an argument.…”
Section: Job Demandsmentioning
confidence: 84%